EMOTIVENESS OF PROSODY OF BRITISH DIALOGIC SPEECH - Jurayeva , Dilorom Rakhmatillo qizi (INTERNATIONAL CONFERENCES, 2023)
Human beings express their ideas not only by sentence itself but also by their melody of speech. Inclusion of intonation changes the sense of a sentence. As a result, we can convey different meanings with one sentence. And this phenomenon is often produced with the help of intonation, pitch, stress and other ways of expressing further meaning to speech. In dialogic speech it becomes more obvious that we use prosody most. In linguistics, the term prosody is used as a conclude notion for above mentioned words.